Mental Health Revolution: Menghadapi Tantangan Kesehatan Mental Di Era Modern - Negara, Rayzona Yudha (Utami Publisher, 2024)
Mental health has become a critical issue in the modern era characterised by rapid social, economic, and technological change. The mental health revolution reflects global awareness and efforts to address this issue through education, early intervention, and digital technology. This article discusses the challenges of mental health in the modern era, the factors that influence it, and the solutions that can be implemented to support mental health in a sustainable manner. Technology such as mental health apps and online therapy are important innovations, but a holistic approach involving social support, healthy work environment, and mental awareness education is needed.